Positive Fluid Balance as a Prognosis Predictor in Pediatric Sepsis Patients: A Retrospective Cohort Study - Siti Aizah Lawang; Idham Jaya Ganda; Hadia Angriani; Ratna Dewi Artati; Jusli; Gosal, Astri (Faculty of Medicine, Hasanuddin University., 2023)
Introduction: Sepsis is one of the leading causes of infant and child morbidity and mortality worldwide. Fluid administration is an important way to reduce morbidity and mortality in septic patients with low blood flow and shock, since sepsis is often linked to low blood volume. The purpose of this study was to investigate the relationship between positive fluid balance and the outcome of pediatric sepsis patients. Methods: A retrospective cohort analysis of 80 pediatric patients diagnosed with sepsis using the 2005 International Pediatric Sepsis Consensus Conference (IPSCC) criteria. The positive fluid balance value was obtained from medical records and was evaluated using the Receiver Operating Characteristic (ROC) curve method. Results: Positive fluid balance was found to have a significant link with the outcome of pediatric sepsis patients (p<0.05).The positive fluid balance value of ≥4.61% was associated with mortality in pediatric patients with sepsis, with a sensitivity value of 62.79%, specificity of 62.16%, negative predictive value of 58.95%, and positive predictive value of 65.85%. The value of fluid balance in the first 24 hours of Pediatric Incentive Care Unit (PICU) care was higher in septic pediatric patients who died compared to those who improved, but not significantly (p=0.37). The value of total fluid balance during PICU care was higher in septic pediatric patients who died compared to those who improved (p<001). Conclusions: Positive fluid balance with a cut-off value of 4.61% can be used as a prognostic factor in pediatric patients with sepsis.